Advanced practice radiation therapist led vaginal vault brachytherapy: An evaluation of efficiency and effectiveness of service delivery - Rhona Goodwin (Technical Innovations & Patient Support in Radiation Oncology)
Aims: An advanced practice radiation therapist (APRT) role in vaginal vault brachytherapy (VBT) was first introduced in 2015. The aim of this manuscript was to clarify how the introduction of an APRT can improve efficiencies within service delivery while maintaining non inferior clinical outcomes of recurrence. Materials and methods: This was a single-centred retrospective comparative service evaluation of stage 1 endometrial cancer patients treated with postoperative high dose rate VBT alone. Sixty patients in total were included in the evaluation. They were divided into two equal groups of ‘before’ and ‘after’ based on the introduction of the APRT-led role and changes made to treatment processes. Quantitative analysis of waiting times from surgery to adjuvant VBT (weeks), duration of day one treatment procedure (minutes), rate of isolated vaginal recurrence and loco regional recurrence (vaginal and pelvic) were compared between the groups. Results: The mean time from surgery to treatment between the ‘before’ and ‘after’ groups was 13.1 and 9.1 weeks respectively. The mean time for day one treatment procedure was 91 min in the ‘before’ group and 59 min in the ‘after’ group. Vaginal free recurrence (VFR) was 100 % for both groups.. Conclusion: An APRT led vaginal vault service, with learnt role extension, allows for a more efficient and effective service delivery.